Synthesis of chromium-nickel nanoparticles prepared by a microemulsion method and mechanical milling - Ban, Irena (Acta chimica slovenica, 2013)
A chemical and a physical method have been applied for the preparation of chromium-nickel alloy nanoparticles. These particles were designed to be used for controlled magnetic hyperthermia applications. Microemulsions with Ni2+ and Cr3+ and/or NaBH4 as precursors were prepared using the isooctane/CTAB, n-butanol/H2O system. The samples of CrxNi1-x nanoparticles with the desired composition were obtained after the reduction of their salts with NaBH4 and afterwards heat treated in a TGA in a N2 atmosphere at various temperatures. The CrxNi1-x materials were also prepared by mechanical milling. Utilizing a ball-to-powder mass ratio of 20 : 1 and selecting the proper alloy compositions we were able to obtain nanocrystalline CrxNi1-x particles. Thermal demagnetization in the vicinity of the Curie temperature of the nanoparticles was studied using a modified TGA-SDTA method. The alloy's phase composition, size and morphology were determined with XRD measurements and TEManalyses.
Keywords: Curie point; krom; magnetic hyperthermia; magnetic nanoparticles; magnetna hipertermija; magnetni nanodelci; mechanical alloying; nanozlitine; nikelj